Do safety briefings improve patient safety in the acute hospital setting? A systematic review. (30th April 2019) - Ryan, Sharon; Ward, Marie; Vaughan, David; Murray, Bridget; Zena, Moore; O'Connor, Tom; Nugent, Linda; Patton, Declan
Abstract: Aims: To synthesize current knowledge about the impact of safety briefings as an intervention to improve patient safety. Background: Improving safety in health care remains an ongoing challenge. There is a lack of evidence underpinning safety enhancing interventions. Design: Mixed method multi‐level synthesis. Data Sources: Four health literature databases were searched (Cinahl, Medline, Scopus and Health Business Elite) from January 2002 – March 2017. Review Methods: Thomas and Harden approach to mixed method synthesis. Results: Following quality appraisal, 12 studies were included. There was significant heterogeneity in study aims, measures, and outcomes. Findings showed that safety briefings achieved beneficial outcomes and can improve safety culture. Outcomes included improved risk identification, reduced falls, enhanced relationships, increased incident reporting, ability to voice concerns, and reduced length of stay. Conclusion: Healthcare leaders should embrace the potential of safety briefings by promoting their effective use whilst allowing for local adaptation. Abstract : 目的: 综合目前有关将安全简报作为改善患者安全状况的干预措施等影响。 背景: 设计: 采用混合法, 实现多级合成。 数据来源: 2002年1月至2017年3月间, 共对四大健康文献数据库进行文献检索(Cinahl、Medline、Scopus以及Health Business Elite)。 评估方法: Thomas和Harden两位作者都采用混合法, 实现多级合成。 结果: 完成质量评估之后, 共开展了12项研究。其中, 研究目的、研究方法和研究结果均存在显著的异质性。研究结果表明, 安全简报的发布可产生有益的效果, 并可同时改善安全文化。结果包括:风险识别性能改善、失败率降低、关系增进、事件报告数量增加、表达担忧能力的获取以及住院时间的缩短。 结论: 医疗保健领导者应充分利用安全简报的潜力, 促进其有效使用, 并应在使用过程中充分考虑当地具体的适应情况。